Endothelial ganglioside GM3 regulates angiogenesis in solid tumors - Suzuki, Mira; Nagane, Masaki; Kato, Kazuhiro; Yamauchi, Akinori; Shimizu, Takuto; Yamashita, Hiroko; Aihara, Naoyuki; Kamiie, Junichi; Kawashima, Nagako; Naito, Shokichi; Yamashita, Tadashi (Biochemical and biophysical research communications, 2021)
Cancer cells require oxygen and nutrients for growth, making angiogenesis one of the essential components of tumor growth. Gangliosides, constituting membrane lipid rafts, regulate intracellular signal transduction and are involved in the malignancy of cancer cells. While endothelial cells, as well as cancer cells, express vast amounts of gangliosides, the precise function of endothelial gangliosides in angiogenesis remains unclear. In this study, we focused on gangliosides of vascular endothelial cells and analyzed their functions on tumor angiogenesis. In human breast cancer, GM3 synthase was highly expressed in vascular endothelial cells as well as immune cells. Angiogenesis increased in GM3S–KO mice. In BAEC, RNA interference of GM3S showed increased cellular invasion and oxidative stress tolerance through activation of ERK. In the breast cancer model, GM3-KO mice showed an increase in tumor growth and angiogenesis. These results suggest that the endothelial ganglioside GM3 regulates tumor angiogenesis by suppressing cellular invasion and oxidative stress tolerance in endothelial cells. •GM3S is expressed in endothelial cells of breast cancer.•Angiogenesis increases in GM3S knock out mice.•GM3 deficiency increased cellular invasion and oxidative stress tolerance through ERK activation in endothelial cell.•Tumor angiogenesis and growth increase in GM3S knockout mice.